Answer:
I chose the next points:
A(1, 1)
B(2, 3)
C(3,2)
In the picture attached, the triangle is shown.
Translation of point A to the origin
The new triangle is:
A'(0, 0)
B(2, 3)
C(3,2)
90° rotation around point B
90°counter-clockwise rotation about the origin transforms (x, y) into (-y, x)
90°counter-clockwise rotation around a point (2,3) is doing as follows: subtract the point, rotate around origin, add the point back:
A(1,1) → (-1, -2) → (2, -1) → A'(4, 2)
C(3,2) → (1, -1) → (1, 1) → C'(3,4)
The new triangle is:
A'(4, 2)
B(2, 3)
C'(3,4)
Reflection of the triangle across the x-axis
Reflection across x-axis transforms (x, y) into (x, -y). Then:
A(1, 1) → A'(1, -1)
B(2, 3) → B'(2, -3)
C(3,2) → C'(3,-2)